MANAJEMEN PESANTREN AZ-ZIKRA PENDEKATAN MANAJEMEN SYARIAH - Batubara, Amrizal; Misno; Chaniago, Asdi (Institut Agama Islam Sahid Bogor, 2024)
This thesis aims to analyze the implementation of management at the Az-Zikra Sentul Islamic Boarding School. This is interesting because after the death of Muhammad Arifin Ilham as the founder of this institution experienced a setback. The research method used in this study is a case study with qualitative data. Data obtained through direct observation, interviews and document study. The analysis was carried out using data triangulation and member checking to ensure that the data is truly valid and can be accounted for. Implementation of Management at the Az-Zikra Islamic Boarding School Sentuk City, Bogor is carried out in accordance with a modern management pattern where the organizational structure and division of labor have been going well. This can be seen from the complete facilities and pre-facilities available, curriculum that is running well, funding is running smoothly, teaching and learning activities are running smoothly, human resource management is good and the pattern of leadership that is already running. The management of the Az-Zikra Islamic Boarding School in Bogor has followed a sharia management system in which every program carried out is based on Islamic sharia values. Leadership that is based on Islamic values, HR management is also aligned with Sharia HR management, syar'i teaching and learning activities, a financial system that already follows Islamic financial management to other well-available prayer facilities. All of this shows that indeed the Az-Zikra Islamic boarding school in its management is in accordance with the existing sharia management system